PEMANFAATAN FLASHCARD DALAM PENGENALAN VOCABULARY PADA SISWA TK AL-AQOBAH II - Sri Endah Kusmartini (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The importance of developing students' skills, including English skills was realized by the teachers of TK Al-Aqobah II, but they experienced problems when trying to introduce the vocabulary to students. The writer offered training regarding the use of flashcards to introduce vocabulary to the students of kindergarten. The following were the steps: first, the writer made preparations regarding the training; next, the writer gave a pre-test; based on the results of the pre-test, the writer delivered the training; finally, the writer gave the post-test. The results showed that the teachers understood the benefits of flashcards and they had the capabilities to use these flashcards in order to introduce vocabulary to the students with a mastery level of 80%. A slight obstacle faced by the teachers was the educational background of the teachers who were not from English Education. These obstacles can be overcome with training and mentoring conducted by the writer.